A turn-on phosphorescent sensor of Pb2+ in water by the formation of a coordination polymer. Issue 12 (20th February 2019) - Villa, Marco; Roy, Myriam; Bergamini, Giacomo; Gingras, Marc; Ceroni, Paola
Abstract : Persulfurated asterisks functionalized with six carboxylic groups form a strongly green phosphorescent coordination polymer upon addition of Pb 2+ ions in aqueous solution. The self-assembly process is selective and reversible, enabling Pb 2+ sensing with a detection limit of 6.0 × 10 −7 M. Abstract : Hexakis(phenylthio)benzene compounds carrying six carboxylic acid groups at their periphery combine aggregation-induced phosphorescence, water-solubility and metal-binding properties: the para -isomer is a selective and sensitive turn-on phosphorescent sensor of Pb 2+ ions in water.